Enhancing SME Product Brand Equity in The Digital Age as Strategic Approaches in the Era of Artificial Intelligence - Indrasari, Meithiana; Syamsudin, Nur; Tampubolon, Liosten Rianna Rosida Ully (International Journal of Business, Law, and Education, 2024)
This research explores the role of strategic approaches in enhancing Small and Medium-sized Enterprises' (SMEs) product brand equity in the digital era. It focuses on the integration of Artificial Intelligence (AI) technologies, highlighting the opportunities and challenges SMEs face in enhancing their brand equity. The study evaluates various strategies for SMEs to navigate the digital complexities, including machine learning algorithms, natural language processing, and predictive analytics, to refine brand positioning, customer engagement, and personalized experiences. It also explores ethical considerations and potential risks associated with AI adoption, offering insights into maintaining consumer trust and ethical practices. The research synthesizes theoretical frameworks with practical implications, contributing to the understanding of strategic paradigms for SMEs to thrive in the digital age. The findings aim to provide actionable insights for SMEs and stakeholders to craft robust strategies aligning with AI capabilities, fostering sustainable brand equity growth and competitive advantage.